Electronic Structure of Thiolate‐bridged Diiron Complexes and a Single‐electron Oxidation Reaction: A Combination of Experimental and Computational Studies. Issue 9 (12th July 2016) - Chen, Si; Luo, Lun; Li, Yang; Yang, Dawei; Qu, Jingping; Luo, Yi
Abstract: Single‐electron oxidation of a diiron‐sulfur complex [Cp*Fe( μ ‐bdt)FeCp*] (1, Cp*= η 5 ‐C5 Me5 ; bdt=benzene‐1, 2‐dithiolate) to [Cp*Fe( μ ‐bdt)FeCp*] + (2 ) has been experimentally conducted. The bdt ligand with redox‐active character has been computationally proposed to be a dianion (bdt 2− ) rather than previously proposed monoanion (bdt ·− ) radical in1 though it has un‐equidistant aromatic CC bond lengths. The ground state of1 is predicted to be two low‐spin ferrous ions ( S Fe =0) and2 has a medium‐spin ferric ion ( S Fe =1/2) and a low‐spin ferrous center ( S Fe =0), and the oxidation of1 to2 is calculated to be a single‐metal‐based process. Both complexes have no significant antiferromagnetic coupling character. Abstract : The oxidation of1 to2 is calculated to be a Fe2‐based process (see the Figure above). The bdt is a dianion ligand in complex1 and2 rather than previously proposed monoanion radical.